Peledakan Penyakit Karat Merah Alga Pada Tanaman Gambir (Uncaria gambii) Di Babat Tomat, Sumatera Selatan (PEST Tropical Journal, 2003)
An algal red rust disease was found occuring on all observed tree of three hagambir plantings in Babat Toman Region, South Sumatra during dry season in 2002.The disease is caused by the green alga Cephaleuros sp. of the familyTrentepholiaceae and the division Clorophyta. The algae causes mild leaf spots onyoung trees (7 months-old). On old trees (9 years-old), the algae was found infectingmore severily, causing severe defoliations and dead of twigs and branches. Thisoutbreak may be induced by the low soil fertility, dryness, over-harvesting, and poorsanitation.